MODEL CITRA TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM MEMBANGUN EKUITAS MEREK - , MAHRINASARI MS; , Prof. Dr. Basu Swastha Dharmmesta, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to develop and test the model of corporate social responsibility (CSR) image in building brand equity, as empirical support for the model proposed by Chahal and Sharma (2006) and Hoeffler and Keller (2002). The main objective of this research is to examine the comparative effect among the Carrollâs CSR dimensions (1979, 1991, 1999), company credibility, and CSR communication on CSR image. Other research objectives are to test CSR image as the mediating effect in the effect of CSR dimensions and CSR communication on brand equity, to examine the effect of brand equity on brand preference and purchasing intention mediated or without mediated by brand preference, and to prove the effect of brand preference on purchase intention. Data of 564 respondents, individually potential consumers knowing the CSR activity, never buying the products or services produced by the company implementing CSR, having ever seen and or seeing the CSR communication, were collected using online and offline survey and analyzed using Two Step Approach of SEM (Structural Equation Modeling). The main finding of this research is that while CSR communication has the greatest role in creating positive CSR image, compared to CSR dimensions and company credibility, economic responsibility has no significant effect both on CSR image and brand equity. Other important findings are 1) CSR image acts as a mediating variable, giving the estimated value of CSR communication effect on brand equity is greater than the estimated value of the ethical-legal responsibility effect on brand equity, so it suggests that CSR communication can be as a strategic tool to eliminate the stakeholdersâ skepticism toward the CSR activity, that is manifested in the formation of the positive image of CSR. This also will have an impact on building strong brand equity value